2022
DOI: 10.4103/jisp.jisp_684_20
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the regenerative potential of different types of platelet concentrates in periodontal intrabony defect management

Abstract: This systematic review aims to compare the regenerative potential of different preparations of platelet concentrates in periodontal osseous defect regeneration. A comprehensive search was conducted on PubMed, Cochrane, and Medline electronic databases including articles published till April 2020. Search was performed as per Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Of the total 224 studies fetched for the study, 7 were found relevant and included. Studies with a follow-up p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Another systematic review done by Reshma AP et al 35 , also concluded that limited evidence was reported regarding the superiority of PRF over PRP and T-PRF over PRF for the treatment of osseous defects. There was no significant difference among the platelet concentrates.…”
Section: Figure 3: Shows the Image Of The T-prf Membrane Placed In Th...mentioning
confidence: 99%
“…Another systematic review done by Reshma AP et al 35 , also concluded that limited evidence was reported regarding the superiority of PRF over PRP and T-PRF over PRF for the treatment of osseous defects. There was no significant difference among the platelet concentrates.…”
Section: Figure 3: Shows the Image Of The T-prf Membrane Placed In Th...mentioning
confidence: 99%